Ressonância magnética na avaliação das articulações do pé de pacientes com artrite reumatoide - Rondina, Ronaldo Garcia (2016)
Purpose: Study the joints of the clinically dominant foot of patients with rheumatoid arthritis by MRI using RAMRIS score and correlate with clinical data regarding disease activity and functional capacity, measured respectively by DAS28 and HAQ scores. Methods: Cross-sectional descriptive study of fifty-five patients diagnosed with RA followed by the rheumatology division of the Hospital Cassiano Antonio Moraes of the Federal University of Espírito Santo between February and December 2014. The patients' clinically dominant foot was assessed by MRI and clinical and laboratory data were collected to measure the DAS28. Results: Our study demonstrated a linear relationship between the degree of joint involvement, measured by the RAMRIS, with the loss of functional capacity, assessed by HAQ questionnaire. There was also a linear relationship between the score that measures disease activity (DAS28) and HAQ. There was no statistical relationship between the degree of joint involvement, measured by RAMRIS, and DAS28. Conclusion: We conclude that the assessment by MRI can document a state of persistently active disease despite clinical remission assessed by DAS28 score.